CFD Analysis on Cold Storage to Find Out the Effect of Desiccant Material on Relative Humidity - Shalini Singh (AG Volumes, 2021)
Cold storage or refrigerated warehouses are facilities where perishable foodstuffs are handled and stores under controlled temperatures with the aim of maintaining quality. The study attempted to bring down the humidity as well as temperature within the best required range to keep the onions fresh for a longer period of time. A duct was added in the cold storage system. A desiccant material of blue gel silica is used to maintain the humidity and a fan is used to circulate the cold storage air. Both the desiccant material as well as fan was mounted inside the duct pipe. The results obtained were satisfactory and exhibited evidently in the study. For simulation 3 ton and 6-ton cold storage is selected for 2 cases. Simulation is done for checking the proper requirement of keeping onion, apple and potato for longer period. Humidity has wise impact on onion, for controlling humidity within the requirement range desiccant material (Blue silica gel) is used.